1982
DOI: 10.1029/jb087ib06p04595
|View full text |Cite
|
Sign up to set email alerts
|

Source parameters of the 1980 Mammoth Lakes, California, earthquake sequence

Abstract: From the more than 1500 Mammoth Lakes earthquakes recorded on three‐component digital seismographs (Spudich et al., 1981), 150 were used in an analysis of the locations, mechanism, and source parameters. A composite fault plane solution of nine earthquakes 3.9 ≤ M ≤ 5.1 defines a right‐lateral strike slip mechanism on a steeply dipping nearly east‐west plane striking S75°E or left‐lateral strike slip on a nearly north‐south plane striking N10°E. Vertical cross sections of well‐located aftershocks indicate poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
114
0
6

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(132 citation statements)
references
References 26 publications
12
114
0
6
Order By: Relevance
“…A magnitude calibration with β 1:1 is consistent with previous calibrations of the local magnitude scale for small earthquakes (Bakun and Lindh, 1977;Archuleta et al, 1982;Bakun, 1984b, Fletcher et al, 1984. For comparison with this scaling, also plotted in Figure 7 is a line with β 1:5 (dashed curve), the slope expected for moment magnitudes M w .…”
supporting
confidence: 67%
See 2 more Smart Citations
“…A magnitude calibration with β 1:1 is consistent with previous calibrations of the local magnitude scale for small earthquakes (Bakun and Lindh, 1977;Archuleta et al, 1982;Bakun, 1984b, Fletcher et al, 1984. For comparison with this scaling, also plotted in Figure 7 is a line with β 1:5 (dashed curve), the slope expected for moment magnitudes M w .…”
supporting
confidence: 67%
“…It is thus unsurprising that the scaling between moment and catalog magnitude can vary somewhat with location and with the magnitude range considered (e.g., Bindi et al, 2005;Castello et al, 2007;Edwards et al, 2010;Gasperini et al, 2013). For instance, Wyss et al (2004) examined small earthquake moments near Parkfield, California, and found a scaling parameter β of 1.6 for duration magnitudes, larger than the β of 1.0-1.3 previously obtained for small events on the local magnitude (M L ) scale (Bakun and Lindh, 1977;Archuleta et al, 1982;Bakun, 1984b, Fletcher et al, 1984. Abercrombie (1996) found that β ≈ 1:0 near Cajon Pass when comparing with the Southern California Seismic Network magnitudes, and Ben-Zion and Zhu (2002) noted that β increased to 1.3 for M L > 3:5 earthquakes.…”
Section: Introduction: Background On Magnitude Estimatesmentioning
confidence: 83%
See 1 more Smart Citation
“…Other studies, where the majority of magnitudes are below 4, find similar values. For example, Archuleta et al (1982) find M L ∼ 1:56 0:1M w for 3 ≤ M L ≤ 6, in a study of source parameters for 40 earthquakes within a sequence of 1500 events at Mammoth Lakes, California; Kim et al (1989) find M L ∼ 1:49 0:05M w for earthquakes in the magnitude range of 2 ≤ M L ≤ 5:2, in a study of source parameters for earthquakes in the Baltic Shield. Many other studies find values between 1 and 1.9 over various magnitude ranges (see Deichmann [2006] and Hanks and Boore [1984] for a compilation).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Most of the observational studies in the seismological literature investigated scaling relationships characterizing different seismic areas and different seismotectonic environments or some particular pattern of seismicity (Cocco and Rovelli, 1989;Somerville et al, 1987). An interesting application of source parameters estimation uses seismic sequences to investigate the stress levels, the radiated energy and the mechanism of stress release (Archuleta et al, 1982;Fletcher and Boatwright, 1991;Mori et al, 2003).…”
Section: Introductionmentioning
confidence: 99%